2022
DOI: 10.3389/fchem.2022.1053532
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and biological activities of zinc(II), copper(II) and nickel(II) complexes of an aminoquinoline derivative

Abstract: Interest is increasingly focused on the use of transition metal complexes as biochemical, medical, analytical, pharmaceutical, agronomic, anticancer, and antibacterial agents. In this study, three complexes of [Zn(H2L)Cl] (1), [Cu(H2L)(H2O)(NO3)] (2) and [Ni(H2L)(NO3)].2H2O (3) were synthesized from a 2-chloroquinoline-3-carbaldehyde derived ligand [H3L = ((E)-2-(((2-((2-hydroxyethyl)amino)quinolin-3-yl)methylene)amino)ethanol. The compounds were characterized using physicochemical and spectroscopic methods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Thus, we reasonably concluded that the coordination of chrysin was via its carbonyl oxygen . There was little red shift (6 and 2 nm) in complex 2 , which could be due to the predominant electron transfer raised from interligands, absence of d → d transition, and higher band gap energy in the Zn­(II) complex as a result of d 10 electron configuration . Moreover, the absence of a peak above 400 nm for complex 2 could be due to nonexiting ligand-to-metal charge transfer bands in Zn­(II) metal-centered complexes (Figure ).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Thus, we reasonably concluded that the coordination of chrysin was via its carbonyl oxygen . There was little red shift (6 and 2 nm) in complex 2 , which could be due to the predominant electron transfer raised from interligands, absence of d → d transition, and higher band gap energy in the Zn­(II) complex as a result of d 10 electron configuration . Moreover, the absence of a peak above 400 nm for complex 2 could be due to nonexiting ligand-to-metal charge transfer bands in Zn­(II) metal-centered complexes (Figure ).…”
Section: Resultsmentioning
confidence: 73%
“…The quantum chemical descriptors of the free ligands and the corresponding metal complexes are presented in Figure and Table S2, whereas the wave function distributions are shown in Figures and S3. In our previous study, we reported that the band gap energy ( E g ) has a strong correlation with various biological activities: antibacterial, antioxidant, and cytotoxicity. ,, Moreover, band gap energy has been used as an important stability descriptor. A compound with large band gap energy is suggested to be stable and hard, whereas that with small band gap energy is less stable, giving the compound softness and enhanced biological importance .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DPPH scavenging activities of the synthesized complexes (Cr1 and Cr2) were evaluated as we described previously, with minor modifications (Lemilemu et al, 2021;Alem et al, 2022;Damena et al, 2023). The percent DPPH free radical scavenging activities of the synthesized complexes and the standard were calculated using Equation (1).…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…The calculated absorption spectra were red-shifted by 30 nm for better comparison with the corresponding experimental spectra. Quantum chemical descriptors calculation, frontier molecular orbital (FMO) visualization, and associated data were conducted as we previously reported (Alem et al, 2022;Damena et al, 2023).…”
Section: Quantum Chemical Studiesmentioning
confidence: 99%